El Triásico de la región de Monterde-Albama de Aragón (Provincia de Zaragoza). - Arche, A.; Rincón, R.; Vilas, Lorenzo; García Quintana, Álvaro; Hernando Costa, S. (Cuadernos de Geología Ibérica, 1977)
Sin resumen